Period Power: Organizational Stigma, Multimodality, and Social Entrepreneurship in the Menstrual Products Industry - Werner, Mirjam D.; Punzi, Maria Carmen; Turkenburg, A. J. K. (Journal of Management Studies, 2024)
In this article, we contribute to the recent direction in the organizational stigma literature that focuses on stigma as providing opportunities for organizations. Drawing on a qualitative abductive study of 90 social enterprises in the menstrual products industry, we extend the literature by showing how the organizational form of social enterprises allows them to put the societal issue of menstruation stigma at the core of their ventures. Specifically, we find that these social enterprises take a disruptive strategy, and we elaborate on the tactics of normalization and moralization on which they draw by highlighting the essential role of multimodality in the process of destigmatizing menstruation. In light of the tabooed nature of menstruation, this multimodal approach is key to challenging existing hidden, taken‐for‐granted norms around menstruation and supplanting them with alternative ones. Our study has important implications for the literatures on organizational stigma, social enterprises, and multimodality and points to their strong conceptual complementarity for understanding processes of societal change.